Investigation of eating behaviors in high school students - Cetin, Semra (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate the eating behaviors of high school students. Methods: A cross-sectional study was designed as a research method. The sample of the study consisted of a total of 236 (115 female and 121 male) high school students. As data collection tools, "the eating behavior scale" was used. Since the data were normally distributed, the independent sample t-test was used. Results: The mean age of females and males were 16.40 and 16.69, respectively. There were statistically significant differences between both healthy eating behavior scores and unhealthy eating behavior scores according to gender (p<0.05). According to gender, eating behaviors did not find statistically different (p>0.05). While there was no difference between the healthy eating behaviors of the students according to their sporting status (p>0.05), the score of unhealthy eating behaviors, sportsmen’s score was significantly lower (p<0.001). There was no statistically significant difference in sporting status compared to sports in eating behaviors (p>0.05). Conclusion: While healthy and unhealthy eating behaviors of high school students vary according to gender, it was concluded that general eating behaviors are similar. In addition, it was determined that the students who are engaged in sports have worse eating behaviors than those who do not do sports. It has been considered that all high school students and especially sports students need to change their eating habits with the help of their parents or their instructors.